Western diet affects the murine circadian system possibly through the gastrointestinal microbiota. Issue 2 (4th March 2017) - Refinetti, Roberto
Abstract: Consumption of a high-fat diet characteristic of human Western diet has been shown to affect the circadian system of laboratory rodents. The present study confirms an effect of Western diet on the circadian system of mice, specifically a shortening of the free-running circadian period of running-wheel activity, in addition to increased weight gain. Decimation of the gut microbiota by broad spectrum antibiotic treatment reversed the effect of Western-diet feeding on the free-running period, which suggests that the effect of Western-diet feeding on the circadian system is mediated by the gastrointestinal microbiota. This finding is particularly relevant in view of recent studies describing a relationship between gut microbes, circadian clock function, and obesity.